Intervención del Terapista Respiratorio en paciente masculino de 45 años con neumonía atípica causada por el Covid-19. - Zapata Orosco, Carolyn Arianna (2023)
Given the rapid increase in new diseases and viral mutations, the different global health organizations have shown their concern because these diseases quickly become or can become a pandemic. In the last 20 years, new diseases have emerged as a result of new viruses such as atypical pneumonia, SARS-CoV, H1N1 influenza, etc. This clinical case study is based on a 45-year-old male patient with atypical pneumonia caused by Covid-19 who was admitted to the emergency department on 09/10/2022 for presenting a three-day clinical picture characterized by dyspnea, fever, cough, disoriented and with abundant nasal secretion, it begins with the evaluation of the signs and symptoms and an oxygen mask with a reservoir is placed on him, the vital signs are monitored and he is referred. Complementary tests are carried out such as: rapid Covid- 19 antigen test, plus complementary tests such as quantitative PCR, chest X-ray and a computed tomography showing what is called ground glass infiltrate. When comparing the values presented by the patient, heart rate 134 beats/min, respiratory rate 32 breaths/min, temperature 38°, SatO2 91%, with the values that are considered within the established normal range, we can verify that there is a serious pathology, which must be treated as soon as possible in order to avoid further complications. Once we have made the diagnosis thanks to the observation of the patient's symptoms and the complementary tests carried out on it, it was concluded that the 45-year-old patient suffers from acute respiratory failure caused by the Covid-19 virus. The medical staff begins a pharmacological treatment to try to reverse this disease and I start with respiratory physiotherapy treatments and maneuvers always under the guidance and medical prescription and according to what I have learned in the classrooms of the University and in my pre-professional practices. 01/14/2022 the relatives sign the voluntary discharge, the flowmeter that has the oxygen tank brought by the relatives is regulated and at 09:30 a.m. the patient leaves the door of the health facility in a wheelchair helped by the nursing staff terminated my intervention in this case.